2015
DOI: 10.1016/j.bbamcr.2015.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Elastic properties of epithelial cells probed by atomic force microscopy

Abstract: Cellular mechanics plays a crucial role in many biological processes such as cell migration, cell growth, embryogenesis, and oncogenesis. Epithelia respond to environmental cues comprising biochemical and physical stimuli through defined changes in cell elasticity. For instance, cells can differentiate between certain properties such as viscoelasticity or topography of substrates by adapting their own elasticity and shape. A living cell is a complex viscoelastic body that not only exhibits a shell architecture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 72 publications
4
36
0
Order By: Relevance
“…The relatively minor but significant effect falls in line with immunofluorescence experiments showing that nocodazole treatment caused only partial depolymerization of microtubules in confluent interphase cells [Fig EV4B; see also (Pepperkok et al , )]. Finally, inhibition of actin polymerization by cytochalasin D reduced the stiffness of both control cells and GFP‐NLP + cells (Fig C), confirming that actin exerts a major contribution to cellular stiffness (Fletcher & Mullins, ; Bruckner & Janshoff, ). Taken together, these results support the notion that NLP‐induced centrosomal aberrations increase cellular stiffness by stabilizing microtubules, which in turn influences the actin cytoskeleton.…”
Section: Resultssupporting
confidence: 79%
“…The relatively minor but significant effect falls in line with immunofluorescence experiments showing that nocodazole treatment caused only partial depolymerization of microtubules in confluent interphase cells [Fig EV4B; see also (Pepperkok et al , )]. Finally, inhibition of actin polymerization by cytochalasin D reduced the stiffness of both control cells and GFP‐NLP + cells (Fig C), confirming that actin exerts a major contribution to cellular stiffness (Fletcher & Mullins, ; Bruckner & Janshoff, ). Taken together, these results support the notion that NLP‐induced centrosomal aberrations increase cellular stiffness by stabilizing microtubules, which in turn influences the actin cytoskeleton.…”
Section: Resultssupporting
confidence: 79%
“…It is therefore of great interest to understand how cells respond mechanically to (bio)chemical and physical stimuli (1, 5, 6). In the case of animal cells, the cell’s mechanical response to deformation originates mainly from the plasma membrane firmly attached to a contractile actomyosin network composed of cross-linked actin filaments as well as motor proteins such as myosin II (7, 15, 16, 17). Living cells are soft composite materials that actively contract under consumption of chemical energy and exhibit both solidlike elastic and fluidlike viscous properties.…”
Section: Introductionmentioning
confidence: 99%
“…Brain cells are among the softest and osteoblasts and chondrocytes among the stiffest. Cell stiffness is highly correlated with the thickness and number of attachment sites of the actomyosin cortex to the membrane, the amount of excess area stored in the plasma membrane, adhesion, and osmotic pressure (7, 8, 15, 16). Severing actin filaments as well as arresting myosin motors can have a drastic effect on the estimated Young’s moduli (7, 8, 34).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, cardiac 32 myocytes, which make up the cardiac muscle, are very stiff with elastic moduli in the 35-42 kPa range 7 . 33 These studies also indicated that mechanical properties of cells correlate with their microenvironment 34 and with cellular processes, including cell division 8 , adhesion 9 , migration 10 , motility 11 and 35 differentiation 12 . Moreover, several human diseases closely correlate with abnormal stiffening of cells, 36 e.g., asthma 13 , vascular disorders 14 and aging 7,15,16 ; or softening of cells, e.g., cancer [17][18][19][20] .…”
Section: Introduction 24mentioning
confidence: 95%
“…This is likely due to their higher-order structures and interaction with crosslinkers and other 18 actin binding proteins. Cells treated with reagents that inhibit actin polymerization, such as cytochalasin 19 D and latrunculin B, showed significantly reduced cell stiffness [29][30][31][32][33] . Conversely, cells treated with 20 nocodazole, which interferes with microtubule polymerization, showed insignificant changes in cell 21 stiffness 29, [32][33][34] .…”
Section: Introduction 24mentioning
confidence: 99%